Dosis de compost de residuos de cosechas de hortalizas y su influencia en el cultivo de Brassica oleracea L., var. botrytis “coliflor”, en Zungarocoha - Loreto.2018 - Pérez Petterman, David (2019)
The Thesis "Doses of compost from vegetable crop residues and their influence on the cultivation of Brassica oleracea L., var. botrytis "cauliflower", in Zungarococha-Loreto.2018", was developed in the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located south of the city of Iquitos-Perú. The type of research was experimental, explanatory, cross-sectional. prospective and longitudinal with one independent variable (compost dose of vegetable crop residues) and seven dependent variables (plant height, plant extension, root length, number of leaves/plant, pella diameter, pella/plant weight and total plant weight). El objetivo general fue determinar las características agronómicas y rendimiento del cultivo de Brassica oleracea L., var. Botrytis “coliflor”. El Diseño experimental utilizado fue el Diseño de Bloques Completamente al Azar, con cuatro tratamientos y cuatro repeticiones. Al final del experimento se llegó a las siguientes conclusiones: compost doses of vegetable crop residues influenced the agronomic characteristics and yield of the crop, where the T3 Treatment (50 t of compost /ha) presented the highest results of plant height (39 cm), plant extension (65 cm), root length (14 cm), pella diameter (14.32 cm), weight of pella/plant (250 g), weight of pellas/ha (5,000 Kg/ha), statistically surpassing the other treatments studied and turning out to be the most profitable with an economic income of S /. 8,025.00.